Educational Management in Shaping Students' Discipline at SMPIT (Junior High School) Plus Dar El Hijrah Ciseeng - Fatimah, Fafat (Jurnal Indonesia Sosial Sains, 2026)
This study aims to determine the role of student management in shaping student character at SMPIT (Junior High School) Plus Dar El Hijrah. This study used a descriptive qualitative approach with observation, interviews, and documentation methods. Then, through data validity testing and conclusion drawing, the data can be presented US research findings. Students at SMPIT (Junior High School) Plus Dar El Hijrah have not yet demonstrated good behavior. This is evident in the many students who violate or refuse to comply with their teachers' instructions. The importance of discipline for students, this study aims to examine student management in shaping student character at SMPIT (Junior High School) Plus El Hijrah. It is hope that the results of this study can contribute to the development of more effective educational strategies in shaping student discipline. The results of this study relate to the formation of student character discipline at SMPIT (Junior High School) Plus Dar El Hijrah, Ciseeng District.